• Помогите!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

    question img
    question img

Ответы 1

  • (\frac{3}{x^2-9}+\frac{1}{3-x})\cdot \frac{x^2-6x+9}{x}=(\frac{3}{(x-3)(x+3)}-\frac{1}{x-3})\cdot \frac{(x-3)^2}{x}=\\\\=\frac{3(x-3)-(x+3)}{(x-3)(x+3)}\cdot \frac{(x-3)^2}{x}=\frac{3x-9-x-3}{x+3}\cdot \frac{x-3}{x}=\frac{2x-12}{x+3}\cdot \frac{x-3}{x}=\\\\= \frac{2(x-6)\cdot (x-3)}{x\cdot (x+3)}
    • Автор:

      cutieg6wo
    • 5 лет назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years